2020
DOI: 10.1177/1078155220929750
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of diffuse large B-cell lymphoma-associated hemophagocytic lymphohistiocytosis

Abstract: Introduction Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and life-threatening syndrome of excessive immune activation. Herein, we aimed to report a diffuse large B-cell lymphoma (DLBCL) case that was presented as HLH. Case report A 32-year-old man presented to a hospital with complaints of vomiting, nausea and diarrhea in October 2019. Fever and hepatosplenomegaly was detected in physical investigation. Bone marrow aspiration investigation revealed the hemaphagocytosis. HLH-2004 protocol was star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The literature review performed for the present study showed recently reported cases of DLBCL with HLH, which were similar to the clinical manifestation of the current patient, but none of them presented with plasmacytic differentiation and MYD88 L265P mutation. Specifically, after R-CHOP chemotherapy, few patients achieved remission ( 23 , 24 ), and others achieved transient remission but relapsed soon after or died immediately ( 25 , 26 ). In the summary of a clinical case series, researchers suggested that after the combination of HLH-directed therapy and malignancy-focused interventions, treatment should be decided on a case-by-case basis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature review performed for the present study showed recently reported cases of DLBCL with HLH, which were similar to the clinical manifestation of the current patient, but none of them presented with plasmacytic differentiation and MYD88 L265P mutation. Specifically, after R-CHOP chemotherapy, few patients achieved remission ( 23 , 24 ), and others achieved transient remission but relapsed soon after or died immediately ( 25 , 26 ). In the summary of a clinical case series, researchers suggested that after the combination of HLH-directed therapy and malignancy-focused interventions, treatment should be decided on a case-by-case basis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…EBV is a less common cause of non-GCB type DLBCL and has been associated with EBV-positive DLBCL of the elderly along with 5 to 10% of DLBCL not otherwise speci ed [4]. These infections can set off immune cascades in the body triggering sporadic cases of secondary HLH [5]. HLH is a life-threatening disorder of immune activation known to be caused by hematologic malignancies, most commonly NK/T-cell lymphomas [6] however it can be uncommonly associated with non-Hodgkin's B-cell lymphomas [7].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography of the abdomen and pelvis with contrast showed splenomegaly measuring 18. 5 *EBV viral capsid antibody (VCA) IgM negative <36, EBV VCA antibody IgG positive >21.9, EBV nuclear antigen antibody negative <18, EBV early antigen IgG positive > 10.9…”
Section: Case Presentationmentioning
confidence: 99%
“…The 5-year OS and RFS of patients who received chemotherapy were significantly higher than those in the patients who did not receive chemotherapy. The aggressive treatment of primary tumors in cases of tumor-associated HPS has been recommended (13,27,31). Although the current study focused on a small number of patients, it indicates that chemotherapy for lymphoma has great potential in the treatment of LAHS, and can improve patient prognosis.…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 91%